Use of chemometric and quantum-mechanical methods in the analysis of bioactive terpenoids and phenylpropanoids against the Aedes aegypti - Reginaldo Bezerra dos Santos; Valdemar Lacerda Júnior; Eustaquio Vinicius Ribeiro de Castro; Vinicius de Oliveira Balthar; Sandro José Greco (Orbital: The Electronic Journal of Chemistry, 2010)
Dengue fever is one of the main public health problems in the world. Many mosquitoes have developed resistance to the conventional insecticides used. Thus, the search for vegetable extracts and natural substances as alternative insecticides has increased. In this study, chemometric methods were employed to classify a group of terpenoid and phenylpropanoid compounds with biological activity against the larval of the A. aegypti mosquitoes. The AM1 (Austin Model 1) method was used to calculate a set of molecular descriptors (properties) for the studied compounds. Then, the descriptors were analyzed using the following methods of pattern recognition: Principal Component Analysis (PCA) and Hierarchical Clustering Analysis (HCA). The PCA and HCA methods have shown to be very effective for the classification of the study compounds in two groups (active and inactive). The electronic variables EHOMO-1, EHOMO-2, ELUMO, ELUMO+2, and the structural LogP were used to classify as active and inactive compounds. In most studied compounds, the variables responsible for separating active from inactive compounds were electronic descriptors. Thus, it can be concluded that electronic effects play a fundamental role in the interaction between biological receptor and terpenoid and phenylpropanoid compounds with activity against larval A. aegypti mosquitoes.